Ecological tax revenue still yields lower pension contributions and higher pensions today - Stefan Bach; Hermann Buslei; Michelle Harnisch; Niklas Isaak (DIW Weekly Report, 2019)
The ecological tax reform that Germany implemented between 1999 and 2003 increased energy tax rates-especially on gasoline and diesel. Today, the ecological tax hikes yield an annual revenue of around 20 billion euros or 0.6 percent of GDP. The money is used to finance a higher federal grant to the public pension scheme. Calculations based on a pension simulation model show that the contribution rate to the statutory pension fund is currently 1.2 percentage points lower and pensions 1.5 percent higher than they would be without the currently higher federal subsidies. A microsimulation analysis found that overall, the ecological tax reform is neutral with regard to revenue and burden. For various income groups and social groups, there are certain levels of burden and relief. For example, the reform relieves middle-income households of employees and retired persons who benefit from the public pension scheme. Households with low incomes are actually burdened, as are commuters with long commutes. These distribution effects should be taken into account in a further development of ecological taxes.
Keywords: H23; Q52; Q58; H55; D31; 330; ecological tax reform; pension reform; redistribution